Penerapan Model Pembelajaran Group Investigation Untuk Meningkatkan Aktifitas Dan Hasil Belajar Siswa Kelas X MIA 7 Madrasah Aliyah Negeri 2 Pekanbaru - Rusmanidar, Rusmanidar (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2022)
This classroom action research aims to test and analyze how much influence the application of the Group Investigation learning model has in Improving Student Activities and Learning Outcomes in Biological Diversity Subject Matters for Class X MIA 7 Madrasah Aliyah Negeri 2 Pekanbaru Odd Semesters Academic Year 2021/2022. This research was conducted using qualitative and quantitative methods based on the principles of the PAKEM method (active, creative and effective learning). The results of this study indicate that the activeness of students at the beginning of the cycle has not been seen significantly but entering the second cycle students become more active, motivated, more challenged. while student learning outcomes experienced a significant increase, namely at the beginning of the cycle the results of student evaluations obtained the value of student incompleteness reaching 57.6% while at the end of the cycle it had reached 16.7%. activeness and student learning outcomes have increased significantly. Based on the results of this study, it can be concluded that the application of the Group Investigation learning model can significantly increase the activity and learning outcomes of students in class X MIA 7 MAN 2 Pekanbaru